(untitled) (Dhaka University Journal of Biological Sciences, 2026)
In Bangladesh monkey performers have a centuries-old tradition to train and use monkeys to perform in road-side gatherings or street shows which allow them to earn their livelihoods and entertain people. A pre-designed questionnaire survey was conducted among 228 monkey performer families at the largest monkey performer’s village at Kashipur of Jhenaidah district between August 2012 and June 2014. Family members of the monkey performers varied from 3 to 12 individuals with the average 6.04. Most of the males and females in this community were married by the ages of 20 and 17 years respectively. Due to their early marriage, they experienced a very high rate of child mortality, especially among those couples who intermarried (78%) within their community. A total of 101 child deaths were recorded among 228 households, of which 83.2% was female and 16.8% was male. A strong positive correlation (r = 0.88) was detected between intermarry and marriage with cousins. Among this community, most of the families (47.1%) had 3 to 5 children. Monkey performance is the main occupation of males (64.5%) while selling of traditional medicine is the main occupation of females (56.5%) in this community. Their daily income ranged from Tk. 200-500 with the average income was Tk. 300 per day. Most of the performers (41.2%) were found to change their performing group for better income opportunity. They had a little access to health care and vaccination. Only 42.1% members got childhood vaccine. In this community most of the people (32.8%) had the common gastrointestinal diseases but they also had some infectious diseases like tuberculosis (4.2%), Malaria (13.9%) and Leprosy (1.2%). Their intimate contact with monkeys can increase the chance of transmitting zoonotic diseases between them. Dhaka Univ. J. Biol. Sci. 35(1): 69-82, 2026 (January)